Comparing Two Testing Strategies: Universal versus Symptomatic SARS-CoV-2 Testing in Obstetric Patients - Aderibigbe, Oluyemi A.; Lappen, Justin R.; Albertini, Megan; Gibson, Kelly S. (American Journal of Perinatology, 2021)
Objective To compare universal severe acute respiratory syndrome coronvirus-2 (SARS-CoV-2) testing to symptomatic testing at two large academic centers.Study Design We performed a retrospective cohort study comparing the approach to testing at two academic centers in Northeast Ohio. The study period started with the inception of symptomatic testing for SARS-CoV-2 at both institutions in March 2020. Women younger than 18 years were excluded. The primary outcome was the SARS-CoV-2 positivity rate in symptomatic pregnant patients at both institutions. Our coprimary outcome was the additional positivity rate obtained from universal testing at the University Hospitals. The secondary outcome of interest was the percentage of SARS-CoV-2 screen positive mothers with screen positive neonates. Data were analyzed using Mann–Whitney U test for continuous variables with chi-square and Fisher's exact tests for proportions.Results During the study period, 144 pregnant women with symptoms of coronavirus disease 2019 (COVID-19) were tested at MetroHealth of which 27 resulted as positive for SARS-CoV-2 (18.7% positivity rate). University Hospitals tested 392 pregnant women with symptoms of COVID-19 of which 67 resulted as positive for SARS-CoV-2 (positivity rate 17.0%). In the universal testing program at University Hospitals, an additional 2,870 tests were performed on asymptomatic pregnant women of which 30 were positive for SARS-CoV-2 (1.0% positivity rate).There were no SARS-CoV-2 positive infants in our cohort, and all cases of maternal critical illness occurred in symptomatic patients.Conclusion Universal and symptomatic testing approaches demonstrated similar clinical performance within a single geographic region in obstetric patients.Key Points
Keywords: SARS-CoV-2; COVID-19 testing; pregnancy; universal testing; symptomatic testing